Biocatalytic Michael‐Type Additions of Acetaldehyde to Nitroolefins with the Proline‐Based Enzyme 4‐Oxalocrotonate Tautomerase Yielding Enantioenriched γ‐Nitroaldehydes. Issue 43 (24th September 2013) - Geertsema, Edzard M.; Miao, Yufeng; Tepper, Pieter G.; de Haan, Pim; Zandvoort, Ellen; Poelarends, Gerrit J.
<x xml:space="preserve">Abstract</x> Call me Michaelase: The enzyme 4‐oxalocrotonate tautomerase (4‐OT) promiscuously catalyzes the Michael‐type addition of acetaldehyde to a collection of aromatic and aliphatic nitroolefins with high stereoselectivity producing precursors of γ‐aminobutyric acid (GABA) analogues (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>